Difference equation method for static problem of infinite discrete structures - Pawlak, Zdzislaw; Rakowski, Jerzy (Journal of Civil Engineering and Management, 2002)
The static problem of infinite, regular systems is considered. The structures are treated as discrete ones. The equilibrium conditions are derived using the FEM formulation. The set of infinite number of equilibrium conditions is replaced by one equivalent difference equation and solved in analytical form. Frist Published Online: 30 Jul 2012